THE INFLUENCE OF INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE (Study on Pharmaceutical Companies Listed on the Indonesian Stock Exchange in 2007 to 2012) - Kiasatina Amalia; Andar wati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The purpose of this study is: 1) To analyze the simultaneous influence between intellectual capital which includes Value Added Capital Employed, Value Added Human Capital, Structural Capital Value Added on financial performance 2) To determine the partial influence between intellectual capital which includes Value Added Capital Employed, Value Added Human Capital, Structural Capital Value Added on financial performance and 3) To find out intellectual capital variables that have a dominant influence on the financial performance. This research was conducted at the pharmaceutical company listed on the Indonesia Stock Exchange in 2007 to 2012. In order to know the influence that occurs among the independent variables (Value Added Capital Employed, Value Added Human Capital, and Structural Capital Value Added) on financial performance using the regression analysis, F test and t test were conducted. Type of research is explanatory that is the researchers explain causal relationships between variables through hypothesis testing. Population and sample in this study is a pharmaceutical company listed on the Indonesia Stock Exchange in 2007 to 2012. The sampling technique used is census sampling so it can be determined the total sample of 7 companies and the research instruments were tested using classical assumption test. The hypothesis testing was using the F and t test to analyze the data to be used in Multiple Regression Analysis. The analysis result shows that there are simultaneously and partially significant influence between intellectual capital which include Value Added Capital Employed, Value Added Human Capital, Structural Capital Value Added on financial performance on pharmaceutical company listed on the Indonesia Stock Exchange in 2007 to 2012. Value Added Human Capital variable have a dominant influence on financial performance of the pharmaceutical company listed on the Indonesia Stock Exchange in 2007 to 2012. Key Words: Value Added Capital Employed, Value Added Human Capital, Structural Capital Value Added and Financial Performance